Technological Unemployment, Meaning in Life, Purpose of Business, and the Future of Stakeholders - Kim, Tae Wan; Scheller-Wolf, Alan (Journal of business ethics, 2019)
We offer a precautionary account of why business managers should proactively rethink about what kinds of automation firms ought to implement, by exploring two challenges that automation will potentially pose. We engage the current debate concerning whether life without work opportunities will incur a meaning crisis, offering an argument in favor of the position that if technological unemployment occurs, the machine age may be a structurally limited condition for many without work opportunities to have or add meaning to their lives. We term this the axiological challenge. This challenge, if it turns out to be persuasive, leads to a second challenge, to which managers should pay special attention: the teleological challenge, a topic especially relevant to the broad literature about corporate purpose and governance. We argue that both the shareholder profit-maximization model and its major alternative, stakeholder theory, are insufficient to address the meaning crisis. Unless rebutted, the two challenges compel business leaders to proactively rethink the purpose of business for future society. Otherwise, businesses will be contributors to a major ethical crisis and societal externality in the coming society.